MEDIA DAN POLITIK CITRA DALAM POLITIK INDONESIA KONTEMPORER - Indrayani, Inri Inggrit (Institute of Research and Community Outreach - Petra Christian University, 2009)
The role of media in dinamics of Contemporary Indonesia Politic is slightly changing. Media control toward public opinion lets media become a tool for image creation and contestation in politic. The esence of politic have been reduced, on the other side the image of candidate become strategic isue beyond party program, vision and mision of the candidate. In political image, media change the candidate to be a package product adjusted to market taste instead of placing him as a political figure. Moreover, media represent constituent as political target market that can be influenced through public relations, marketing and ads strategies. Political image is also played by media within news, especially those which related to authorized power and capitalists. The win of candidate is determined by his soft skill in playing political image through the media.